Respuesta :

Answer:

d. [tex]\frac{\sqrt{2}}{2}[/tex]


Step-by-step explanation:

1. The first step is calculate the inverse cosine function shown  in the exercise and substract this resul with π/2, as following:

[tex]cos^{-1}(\frac{\sqrt{2}}{2})-(\pi/2)=(-\pi/4)[/tex]

2. Then you have that:

[tex]cos(-\pi/4)=\frac{1}{\sqrt{2}}[/tex]

3. Simpliying:

[tex]=\frac{\sqrt{2}}{2}[/tex]


answer : option d

[tex]cos(cos^{-1}(\frac{\sqrt{2}}{2})-\frac{\pi}{2})[/tex]

LEts find [tex]cos^{-1}(\frac{\sqrt{2}}{2})[/tex]

Lets assume [tex]cos^{-1}(\frac{\sqrt{2}}{2})= x[/tex]

When we move cos^-1 to the other side then it becomes cos

[tex](\frac{\sqrt{2}}{2})= cos(x)[/tex]

So angle [tex]x=\frac{\pi}{4}[/tex]

Hence , [tex]cos^{-1}(\frac{\sqrt{2}}{2})=\frac{\pi}{4}[/tex]

We replace it in our problem

[tex]cos(\frac{\pi}{4} -\frac{\pi}{2})[/tex]

Now take common denominator 4

[tex]cos(\frac{\pi}{4} -\frac{\pi*2}{2*2})[/tex]

[tex]cos(\frac{\pi-2\pi}{4})[/tex]

[tex]cos(\frac{-\pi}{4})[/tex]

We know cos(-x) = cos(x)

[tex]cos(\frac{-\pi}{4})=cos(\frac{\pi}{4}) [/tex]

[tex]cos(\frac{\pi}{4})=\frac{\sqrt{2}}{2}[/tex]

ACCESS MORE